Environmentally Driven Ecological Fluctuations on the Faroe Shelf Revealed by Fish Juvenile Surveys - Jacobsen, Sólvá; Gaard, Eilif; Hátún, Hjálmar; Steingrund, Petur; Larsen, Karin Margretha Húsgarð; Reinert, Jákup; Ólafsdóttir, Sólveig Rósa; Poulsen, Meinhard; Vang, Helga Bára Mohr (Frontiers in Marine Science, 2019)
Comprehensive late June surveys have for decades been carried out on the Faroe shelf in order to estimate the abundance of juvenile fish – the 0-group. The abundance of cod juveniles has previously been used in recruitment studies, while the ecological implication of the 0-groups has hitherto received less attention. Here we examined the pelagic 0-group stage in four of the main fish species on the Faroe shelf: cod, haddock, Norway pout and sandeel, representing more than 90% of all juvenile fish on the shelf. A positive relationship between length and abundance at the 0-group stage is observed for all juveniles, and the inter-annual variability was highly similar among the four fish species. Based on this knowledge, we produced a new ecological indicator for the central Faroe shelf ecosystem - the 0-group length index. The 0-group length index is characterized by marked peaks in 1984, 1987, 1994, 2000, 2009 and 2017, which appear to be related to the shelf primary production from spring to mid-summer, and possibly to the marine climate surrounding the Faroe shelf. There is a better temporal overlap between the fish larvae and their prey (i.e. small- to medium sized zooplankton) in years with an early and intensive bloom, while late and/or weak blooms lead to unfavorable feeding conditions. We furthermore show that a large abundance of 0-group fish has the potential to graze down and thus regulate the biomass of large-sized zooplankton during late June. In addition to this top-down influence the 0-group fish clearly impact commercial fish stocks and seabird colonies, and our 0-group length index is therefore a key ecological indicator for the state of the entire central Faroe shelf ecosystem.